Recolectores de miel, cazadores de enjambres y criadores de abejas en Perú, Brasil, Cuba, Nepal y Australia (2012-2019) - Samuel Perichon Le Rouzic (Études Caribéennes)
There are more or less technical bee practices wherever humans occupy a territory in which honey bees live. There can be identified three types of practice associated with bees: the gathering of honey, the hunting or trapping of bee colonies and the keeping of (stingless) bees. These different types may be present in the same territory and concern one or several bee species at the same time. Based on the ethnozoological surveys carried out in Peru, Brazil, Cuba, Nepal, and Australia, we will show how the bee breeding may not be practicable in various geographical, cultural, and religious backgrounds. To assist in understanding the analysis of this issue, an evaluation grid was developed using 29 criteria. Use this method to calculate index values and display as a scatter graph. The distribution of the dots suggests the existence of a relationship between the gathering or hunting practices to the breeding practices. The regression line shows that the development of beekeeping leads to an abandonment of local knowledge and traditions about gathering or hunting.